Current Ripple Analysis of New Double-Stator AC Drive Systems - Irham Fadlika; A. N. Afandi; Pekik Argo Dahono (Universitas Ahmad Dahlan, 2015)
This paper presents a current ripple analysis of new double-stator AC drive system. At first, a new double-stator AC drive system is proposed. The aim is to combine the benefits both the multilevel and multiphase system to provide the better performance to drive AC motor. The input and output current ripples of the proposed AC drive system are then analyzed. The current ripples of the proposed AC drive system are then compared to the ones of conventional double-stator AC drive system. Under the same DC input voltage, it is shown that the proposed results in less output current ripple. Under the same output voltage, the proposed AC drive system results in smaller input current and, therefore, fewer losses on the DC power supply. Experimental results are included to show the validity of the proposed concept.